Volume 2: Turbo Expo 2002, Parts a and B 2002
DOI: 10.1115/gt2002-30052
|View full text |Cite
|
Sign up to set email alerts
|

Observations of Flame Behavior in a Laboratory-Scale Pre-Mixed Natural Gas/Air Gas Turbine Combustor From PLIF Measurements of OH

Abstract: The objective of this study was to obtain instantaneous planar laser induced fluorescence (PLIF) images of OH in a laboratory-scale, gas-turbine combustor (LSGTC) with a premixed, swirl-stabilized, natural gas flame. Instantaneous PLIF images of OH were obtained at each of four operating conditions (high swirl and medium swirl at fuel equivalence ratios of 0.80 and 0.65). Comparison of the instantaneous images illustrates the stochastic nature of the flame structure. Pixel by pixel statistical analysis of each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…Before the lean blowoff, the flame tends to oscillate between extinction and reignition phases [25]. It is very similar to the large scale pulsations observed by other researchers in bluff body flame as well as in swirl stabilized combustor as lean blowoff was approached [26][27][28][29]. High heat loss and the presence of large trans verse and axial velocity gradients were believed to be the reasons.…”
Section: Transient Analysissupporting
confidence: 59%
“…Before the lean blowoff, the flame tends to oscillate between extinction and reignition phases [25]. It is very similar to the large scale pulsations observed by other researchers in bluff body flame as well as in swirl stabilized combustor as lean blowoff was approached [26][27][28][29]. High heat loss and the presence of large trans verse and axial velocity gradients were believed to be the reasons.…”
Section: Transient Analysissupporting
confidence: 59%
“…Hertzberg et al [26] also observed this kind of oscillation, and claimed that blow-out was a result of increased ignition times, longer re-circulation zones and local extinction resulting from high instantaneous strain rates. Hedman et al investigated blow-out in a swirl stabilized combustor and observed intense flame oscillations and temporary loss of flame near the lean blow-out [27]. CFD studies by Norton in micro-burners also observe periodic oscillations near extinction [28].…”
Section: Computational Datamentioning
confidence: 93%
“…The combustion facility used for this study is the same as that used by Hedman and coworkers [1][2][9][10][11]. Pyper [12] constructed the laboratory-scale gas turbine test facility, and assisted Warren and Hedman [11] in installing a single Stokes CARS (coherent anti-Stokes Raman Spectrometer) instrument.…”
Section: Combustor Test Facilitymentioning
confidence: 99%
“…This study was part of a series of laser-diagnostic experiments performed on a common combustion apparatus. Companion studies were performed to measure gas velocities using two-component laser Doppler anemometry (LDA) [3] and to obtain instantaneous planar laser induced fluorescence (PLIF) images of OH [1]. These data were obtained principally for evaluation of comprehensive gas turbine combustion models [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%